Linguodidactic issues of teaching written translation - Awezbekova A. J. (Zien Journals, 2022)
The article considered the task of teaching translation teaching methodology and the development of a strategy for generalizing and systematizing the accumulated experience in order to optimize the process of teaching translation as a specialty.
Keywords: linguodidactics; written translation; text; teaching translation